E0462 Relationship between red cell distribution width and complication risk in patients with acute myocardial infarction. (17th November 2010) - Xu, Kaizu; Lin, Liming; Lin, Jinxiu; Zheng, Jiansheng; Cai, Dingnan
Abstract : Objective: To investigate the relationship between red cell distribution width (RDW) level and risk of complication in acute myocardial infarction (AMI) patients; to compare the correlation of RDW with NT-proBNP, cTnI and hs-CRP. Methods: From January 2006 to December 2009, 200 consecutive AMI patients admitted in cardiology department of affiliated hospital of putian university were enrolled. Patients were classified into complication group (n=145) or complication-free group (n=55) according to the presence or absence of new-onset symptomatic heart failure, arrhythmia or cardiac shock. Patients were divided into quartiles based on RDW value (≤12.8%, 12.9%–13.8%, 13.9%–14.7%, ≥14.8%, n=50 in each quartile), and OR of incident complication was calculated by using logistic regression. Correlation of RDW with NT-proBNP, cTnI and hs-CRP was compared by spearman rank correlation analysis. Results: RDW levels in complication group was significantly higher than that in Complication-free group (14.5±0.97 % vs 12.9±0.85%, p<0.05). RDW levels of AMI patients were positively associated with complication risk, after adjustment for estimated glomerular filtration rate, serum ferrum, left ventricular end-diastolic dimension, left ventricular ejection fraction, and plasma NT-proBNP, cTnI and hs-CRP levels, the highest RDW quartile entailed 1.96 times greater risk for complication than the lowest quartile (95% CI 1.34–2.79, P cTnI > hs-CRP (rs=0.31, 0.29 and 0.21 respectively, all p<0.05). Conclusion: Higher RDW is closely associated with increased risk of AMI complication and elevated plasma NT-proBNP and cTnI level.